1996
DOI: 10.1021/om950841s
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecularly Coordinated Low-Valent Organotellurium Complexes Derived from 1-(Dimethylamino)naphthalene

Abstract: A series of low-valent intramolecularly coordinated organotellurium compounds incorporating the 8-(dimethylamino)-1-naphthyl group has been synthesized by the organolithium route. Insertion of elemental tellurium into the Li-C bond of RLi (2) affords the tellurolate RTeLi (3) (R ) 8-(dimethylamino)-1-naphthyl). Oxidative workup of 3 gives dark red ditelluride 4 in moderate yield. Reaction of 2 with "PhTeBr" afforded telluride 5. Interestingly, the reaction of 2 with TeI 2 afforded the stable tellurenyl iodide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 30 publications
3
39
0
Order By: Relevance
“…The tellurenyl chloride (9) having directly bonded electron withdrawing chlorine atom shows a significant downfield shift compared with the ditelluride (8). The 125 Te NMR chemical shift for 8 is relatively more downfield shifted than those of the corresponding reported ditellurides of 1-(N,N-dimethylnaphthyl)amine (461 ppm) [3], N,N-dimethylbenzylamine (375 ppm) [4] having a sp 3 -N donor atom and (R)-4-ethyl-4-hydro-2-phenyl-2-oxazoline (424 ppm) [4], 2-phenyl-2-oxazoline (420 ppm) [4], 4,4-dimethyl-2-phenyl-2-oxazoline (417) [5] and 2-[1-(3,5-dimethylphenyl)-2-naphthyl]-4,5-dihydro-4,4-dimethyloxazole (421 ppm) [6] having a sp 2 -N donor atom. Similarly, the 125 Te NMR chemical shift of tellurenyl chloride (9) is also more downfield shifted than the tellurenyl chlorides based on the 2-[1-(3,5-dimethylphenyl)-2-naphthyl]-4,5-dihydro-4,4-dimethyloxazole (1163 ppm) [6] and 4,4-dimethyl-2-phenyl-2-oxazoline (1203 ppm) [7].…”
Section: Synthesismentioning
confidence: 99%
“…The tellurenyl chloride (9) having directly bonded electron withdrawing chlorine atom shows a significant downfield shift compared with the ditelluride (8). The 125 Te NMR chemical shift for 8 is relatively more downfield shifted than those of the corresponding reported ditellurides of 1-(N,N-dimethylnaphthyl)amine (461 ppm) [3], N,N-dimethylbenzylamine (375 ppm) [4] having a sp 3 -N donor atom and (R)-4-ethyl-4-hydro-2-phenyl-2-oxazoline (424 ppm) [4], 2-phenyl-2-oxazoline (420 ppm) [4], 4,4-dimethyl-2-phenyl-2-oxazoline (417) [5] and 2-[1-(3,5-dimethylphenyl)-2-naphthyl]-4,5-dihydro-4,4-dimethyloxazole (421 ppm) [6] having a sp 2 -N donor atom. Similarly, the 125 Te NMR chemical shift of tellurenyl chloride (9) is also more downfield shifted than the tellurenyl chlorides based on the 2-[1-(3,5-dimethylphenyl)-2-naphthyl]-4,5-dihydro-4,4-dimethyloxazole (1163 ppm) [6] and 4,4-dimethyl-2-phenyl-2-oxazoline (1203 ppm) [7].…”
Section: Synthesismentioning
confidence: 99%
“…As a result, detailed spectroscopic characterization of such compounds has scarcely been reported in the literature. Menon et al [21] have reported a number of stable low valent 1-naphthyl tellurides which incorporate dimethylamino group at C-8 position in the naphthyl ring. Intramolecular TeÁ Á ÁN coordination is found to be responsible for the greater stability of these derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…In each compound the amine/imine nitrogen is coordinated to the tellurium atom which exhibits typical T-shaped geometry (Scheme 83). [170] Furthermore, a series of organoselenium compounds incorporating the 8-(dimethylamino)-1-naphthyl group has been synthesised, this includes stable selenenyl halides 154 (Scheme 83). [171] Very short, although varied Se···N contacts are observed in these species.…”
Section: Napsn Systemsmentioning
confidence: 99%